Rosacea and Helicobacter pylori: links and risks - Lazaridou E; Korfitis C; Kemanetzi C; Sotiriou E; Apalla Z; Vakirlis E; Fotiadou C; Lallas A; Ioannides D (Dove Medical Press, 2017)
Elizabeth Lazaridou,1 Chrysovalantis Korfitis,2 Christina Kemanetzi,1 Elena Sotiriou,1 Zoe Apalla,1 Efstratios Vakirlis,1 Christina Fotiadou,1 Aimilios Lallas,1 Demetrios Ioannides1 1First Department of Dermatology and Venereology, Aristotle University Medical School, Thessaloniki, Greece; 2Department of Dermatology, 401 General Army Hospital, Athens, Greece Abstract: Rosacea is a chronic skin disease characterized by facial erythema and telangiectasia. Despite the fact that many hypotheses have been proposed, its etiology remains unknown. In the present review, the possible link and clinical significance of Helicobacter pylori in the pathogenesis of rosacea are being sought. A PubMed and Google Scholar search was performed using the terms “rosacea”, “H.pylori”, “gastrointestinal disorders and H.pylori”, “microorganisms and rosacea”, “pathogenesis and treatment of rosacea”, and “risk factors of rosacea”, and selected publications were studied and referenced in text. Although a possible pathogenetic link between H. pylori and rosacea is advocated by many authors, evidence is still interpreted differently by others. We conclude that further studies are needed in order to fully elucidate the pathogenesis of rosacea. Keywords: eradication, Helicobacter pylori, pathogenesis, rosacea